'It's like someone is holding your hand, an invisible hand': A grounded theory study of participation and personal recovery in Flexible Assertive Community Treatment - Madeleine Borgh; Ulrika Bejerholm; Elisabeth Argentzell; Annika Lexén (Taylor & Francis Group, 2024)
Background Participation in everyday life and personal recovery is often adversely affected for individuals with complex mental health needs. Flexible Assertive Community Treatment (FACT) is a recovery-oriented service targeting participation in everyday life and personal recovery and is thus important to understand from the perspectives of service users.Aim To explore how service users experience the care and support they receive from FACT as facilitating processes of participation in everyday life and in their personal recovery process.Materials and Methods A constructivist Grounded Theory approach was employed, involving 14 in-depth interviews conducted from January to November 2023 with FACT service users (9 women, 5 men; 23-55 years) within the Swedish adult general Mental Health Services.Results The process of Building genuine relationships between participants and FACT team members enabled Doing as a way of recovering. This was facilitated by how FACT was organised, promoting continuity and flexibility in care and support.Conclusions and significance This study contributes to a greater understanding of how genuine relationships between FACT service users and team members provide opportunities for participation and doing as a means for personal recovery. The results underscore the significance of incorporating an occupational therapy perspective into recovery-oriented services.